Heat flow, thermal anomalies, tectonic regimes and high-temperature geothermal systems in fault zones - Guillou-Frottier, Laurent; Milesi, Gaétan; Roche, Vincent; Duwiquet, Hugo; Taillefer, Audrey (Comptes Rendus. Géoscience, 2023)
The potential of high-temperature $({>}150~\text{°}C)$ geothermal systems in crustal fault zones (fault cores and hundreds of meters wide networks of interconnected fractures in the damage zone) is underestimated. Based on numerical models, we show that topography-driven, poroelasticity-driven as well as buoyancy-driven forces play a significant role in the establishment of shallow (1–4 km) thermal anomalies in fault zones. We investigate the role of permeability, topography, fault dip, tectonic regime and fault geometry on the amplitude of thermal anomalies. Favorable conditions include: (i) a damage zone thickness $>$ 100 m, (ii) a minimum cumulative displacement of 100–150 m and (iii) fault zone lengths of at least one kilometer. Based on these parameters, we propose new potential targets for the geothermal exploration of fault zones in Western Europe.